Surface waviness of weld bead (layer) of GTAW based wire arc additive manufacturing process - Agus Sentana; Syahbardia; Mabel Agung Nugroho; Ario Sunar Baskoro (Magister Teknik Mesin Universitas Pancasila, 2026)
Additive manufacturing has become a focus of industry and research due to the many new developments in processes and systems. This is further strengthened by the trend of resource efficiency, as manufacturing processes towards additive manufacturing offer the possibility of producing close to the required size shape. Additive manufactured products can experience surface imperfections assessed in this study, namely the morphology profile or surface curvature (surface waviness) of the weld bead layer. Generally, surface curvature can be referred to as a